69. Prolonged inhibitory effect of 1 Hz rTMS of the motor cortex on the nociceptive evoked potentials to contralateral hand stimulation. Issue 4 (April 2016) - Testani, E.; Granata, G.; Pazzaglia, C.; Padua, L.; Valeriani, M.
Abstract : There are only few data about the effect of the low frequency motor cortex rTMS (LF-rTMS) on both clinical and experimental pain. Since LF-rTMS should have an inhibitory effect on motor cortex, whose activation is known to reduce experimental pain (Le Pera et al., 2007), one could expect that 1 Hz motor cortex rTMS increases an objective pain measure, such as laser evoked potentials (LEPs). In 8 healthy subjects, we investigated the effect of 1 Hz rTMS of the left motor cortex on LEPs to stimulation of both right and left hand dorsum. LEPs were recorded at 4 different times: baseline, T 0 (immediately after 20 min of 1 Hz rTMS), T  + 20 (20 min after 1 Hz rTMS), and T  + 40 (40 min after 1 Hz rTMS). We found that rTMS modified the amplitude of the N2/P2 LEP component only to right hand stimulation ( F  = 12.06, p  < 0.001), while there was no effect on left hand LEPs ( F  = 0.7, p  = 0.56). Post-hoc analysis showed that the N2/P2 amplitude was reduced at T 0, T  + 20, and T  + 40, as compared to baseline ( p  < 0.01). Instead of the expected facilitatory action of LF-rTMS on pain, our results show that LF-rTMS of the motor cortex inhibits contralateral pain; this effects last up to 40 min after the cortical stimulation.